Perbedaan struktur molekul karet alam dengan proses termal koagulan berdasarkan analisis FTIR - Achmad, Feerzet; Simbolon, Yusril Mahendra; Sinaga, Kristomi Yahya; Az-Zahra, Syifa; Yuniarti, Reni; Bindar, Yazid (Jurnal Rekayasa Proses, 2025)
Rubber is one of the most potential and abundant biological natural resources in Indonesia. This research was conducted to determine the content of compounds contained in rubber after coagulation by means of thermal coagulants. There are 2 (two) thermal coagulants used, traditional using firewood and modern using a laboratory oven. Variations in the weight of the latex used were 0.5 kg, 0.75 kg, 1 kg, 1.25 kg and 1.5 kg. Then the results of the thermal coagulant were subjected to the Fourier Transform Infrared (FTIR) test to see the compound content contained in the rubber. The results of the FTIR test on traditional thermal coagulants at high and medium heat and modern thermal coagulants in the oven showed the typical functional groups of rubber, namely the presence of C-H, C=C and C-C carbon bonds.